Perioperative acute kidney injury and urine output in lower limb arthroplasties. Issue 8 (7th May 2021) - Nikkinen, Okke; Jämsä, Elias; Aaltonen, Toni; Alahuhta, Seppo; Ohtonen, Pasi; Vakkala, Merja
Abstract : Background: This study aimed to evaluate the occurrence and perioperative risk factors of acute kidney injury (AKI) in primary elective hip and knee and emergency hip arthroplasty patients. We also aimed to assess the effect of urine output (UOP) as a diagnostic criterion in addition to serum creatinine (sCr) levels. We hypothesized that emergency arthroplasties are prone to AKI and that UOP is an underrated marker of AKI. Methods: This retrospective, register‐based study assessed 731 patients who underwent primary elective knee or hip arthroplasty and 170 patients who underwent emergency hip arthroplasty at Oulu University Hospital, Finland, between January 2016 and February 2017. Results: Of the elective patients, 18 (2.5%) developed AKI. The 1‐year mortality rate was 1.5% in elective patients without AKI and 11.1% in those with AKI ( P  = .038). Of the emergency patients, 24 (14.1%) developed AKI. The mortality rate was 16.4% and 37.5% in emergency patients without and with AKI, respectively ( P  = .024). In an AKI subgroup analysis of the combined elective and emergency patients, the mortality rate was 31.3% (n = 5) in the sCr group (n = 16), 23.5% (n = 4) in the UOP group (n = 17), and 22.2% (n = 2) in AKI patients who met both the sCr and UOP criteria (n = 9). Conclusion: Emergency hip arthroplasty is associated with an increased risk of AKI. Since AKI increases mortality in both elective and emergency arthroplasty, perioperative oliguria should also be considered as a diagnostic criterion for AKI. Focusing solely on sCr may overlook many cases of AKI.